Realising the potential of local foods in Pacific Island Countries: Promoting the health, nutrition and income benefits - Singh, Sunil; Francis, Judith Ann; Dietershagen, Jana (Technical Centre for Agricultural and Rural Cooperation, 2019)
Consumers in Pacific Island Countries (PICs) have become increasingly reliant on non-traditional and imported processed foods to meet food and nutritional needs. There is need to invest in scientific research and product development of traditional local food crops and seafood to contribute to improving the food, health and nutrition situation in PICs, as well as provide new income-generating opportunities that specially benefit local communities.